Dr. Christoph Wildburger and Dr. John Parrotta at the All Forest Day, COP 18 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Dr. Christoph Wildburger, IUFRO Coordinator, Global Forest Expert Panels and Dr. John Parrotta, Chair, Global Forest Expert Panel on Biodiversity, Forest Management, & REDD+ at the All Forest Day, COP 18 in Doha, Qatar